2010
DOI: 10.1007/s00198-010-1331-1
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mineral density is associated with increased mortality in elderly men: MrOS Sweden

Abstract: Low BMD is associated with a substantial excess risk of death compared to an average BMD, whereas a higher than average BMD has a more modest effect on mortality. These findings, if confirmed elsewhere, have implications for the constructing of probability-based fracture risk assessment tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 22 publications
(52 reference statements)
0
20
0
Order By: Relevance
“…Several studies have found that baseline BMD is inversely related to subsequent mortality in elderly women and men. (7)(8)(9)11,12,34) Further, in a large cohort of white women 65 years of age and older, a greater decline in BMD was associated with increased mortality from all causes and CVD, regardless of initial BMD. (35) The mechanism of this association is unknown.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have found that baseline BMD is inversely related to subsequent mortality in elderly women and men. (7)(8)(9)11,12,34) Further, in a large cohort of white women 65 years of age and older, a greater decline in BMD was associated with increased mortality from all causes and CVD, regardless of initial BMD. (35) The mechanism of this association is unknown.…”
Section: Discussionmentioning
confidence: 90%
“…The present study was from the Swedish stratum of MrOS (n=3014) recruited at medical centres in Gothenburg (n=1010), Malmö (n=1005) and Uppsala (n=999). Details have been described previously [34][35][36]. In brief, men aged 70-81 years were randomly identified using national population registers.…”
Section: Methodsmentioning
confidence: 99%
“…DXA measurements performed with equipment from different manufacturers were converted to a standardized BMD, as previously described [34][35][36][37].…”
Section: Methodsmentioning
confidence: 99%
“…25 Low BMD has shown to be a strong predictor of fracture risk and mortality in older men. 26 AST rapidly decreases testosterone levels to a hypogonadal state and, as a result, a number of studies involving men receiving AST have demonstrated an accelerated bone loss. 6,9,14,15,27--31 A summary of the studies that reported rates of bone loss as a percentage is shown in Table 2.…”
Section: Osteoporosis and Fractures During And Following Astmentioning
confidence: 99%